2018
DOI: 10.1039/c7nr06020c
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the mechanisms that determine the uptake and metabolism of magnetic single and multicore nanoparticles in aXenopus laevismodel

Abstract: Multicore superparamagnetic nanoparticles have been proposed as ideal tools for some biomedical applications because of their high magnetic moment per particle, high specific surface area and long term colloidal stability. Through controlled aggregation and packing of magnetic cores it is possible to obtain not only single-core but also multicore and hollow spheres with internal voids. In this work, we compare toxicological properties of single and multicore nanoparticles. Both types of particles showed modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 53 publications
(44 reference statements)
2
13
0
Order By: Relevance
“…These results correlate with previous work where iron oxide nanoparticle biodegradation was described in this amphibian model (Marín-Barba et al, 2018). Extensive quantitative studies of the long-term fate of iron oxide nanoparticles inside cells have been carried out.…”
Section: Nps Accumulationsupporting
confidence: 88%
See 1 more Smart Citation
“…These results correlate with previous work where iron oxide nanoparticle biodegradation was described in this amphibian model (Marín-Barba et al, 2018). Extensive quantitative studies of the long-term fate of iron oxide nanoparticles inside cells have been carried out.…”
Section: Nps Accumulationsupporting
confidence: 88%
“…Furthermore, it is not uncommon to obtain contradictory results in vitro and in vivo, given the large number of biological processes that occur in the body which are difficult to reproduce in vitro. The early developmental vertebrate model Xenopus laevis has been recently proposed as a potential tool, able to bridge the gap between in vitro cell-based assays and mammalian models of toxicity assessment (Webster et al, 2016;Al-Yousuf et al, 2017;Mamusa et al, 2017;Marín-Barba et al, 2018;Saide, Sherwood and Wheeler, 2018;González-Paredes et al, 2019). The mortality, malformations and growth inhibition of Xenopus laevis have been studied, after exposure with metal oxide-based nanomaterials (γ-Fe2O3, TiO2, ZnO and CuO) in a water contamination scenario (Nations, Long, et al, 2011;Nations, Wages, et al, 2011;Bacchetta et al, 2014;Perelshtein et al, 2015).…”
mentioning
confidence: 99%
“…We found that the proper mounting of the sample into the MPMS system is extremely important. The frequently used configuration for measurements of biological samples is to use standard plastic or gelatine capsules which are inserted into the drinking-straw and fixed by a cotton stopper [ 19 , 21 , 23 , 27 , 32 ]. However, this configuration leads to several problems.…”
Section: Discussionmentioning
confidence: 99%
“…In previous experimental research, SQUID magnetometry was widely used as a tool for determination of the various form of iron. Measurements were done using iron nanoparticles, namely in cell cultures [ 18 , 19 , 20 ], after in vivo treatment in mice [ 21 , 22 ] and also in embryos of Xenopus Laevis [ 23 ]. Using SQUID magnetometry, Janus et al [ 24 ] showed that blood of patients with atherosclerosis was characterised by a higher concentration of ferrimagnetic particles such as Fe 3 O 4 and γ-Fe 2 O 3 (associated with the elevated values of the magnetic saturation ( M s )) and significant changes in the superparamagnetic behaviour characterised with changes in the remnant magnetisation ( M r ) and the magnetic coercivity ( H c ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive literature adopting human cells and mammals to investigate iron NP toxicity (Valdiglesias et al 2015;von Moos et al 2017), only few papers are based on alternative models. The effects of different Fe 2 O 3 NPs were studied in Xenopus (Nations et al 2011;Marin-Barba et al 2018) and in zebrafish (Zhu, Tian, and Cai 2012), while the effects of ZVI and Fe 3 O 4 NPs, in parallel to Fe bioaccumulation and oxidative stress were investigated in early life stages of medaka fish (Chen, Tan, and Wu 2012;Chen, Wu, and Wu 2013).…”
Section: Discussionmentioning
confidence: 99%